1995
DOI: 10.1007/bf00385645
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of basal and induced DNA single-strand breaks detected by the single-cell gel electrophoresis assay in human peripheral mononuclear leukocytes

Abstract: The aim of the reported study was to investigate the reproducibility of the single-cell gel electrophoresis (SCGE) assay in the determination of DNA single-strand breaks (SSBs) and to estimate the statistical requirements when the SCGE assay is used for the detection of genotoxicity in humans. In human peripheral mononuclear leukocytes (PMLs), we repeatedly measured the rate of SSBs after in vitro incubation of cells for 1 h at 4 degrees C in phosphate buffered saline (PBS, basal) or 10 microM or 50 microM H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 15 publications
2
17
1
Order By: Relevance
“…Increased DNA damage by older age as detected by the comet assay was also reported in other studies [46][47][48][49][50][51]. In contrast, there are studies that showed no effect of age on the level of DNA damage [52][53][54][55][56][57][58]. As the children in our study were in the similar age range spreading over only ten years it was difficult to determine if there is an actual age-difference in DNA damage among them.…”
Section: Discussioncontrasting
confidence: 61%
“…Increased DNA damage by older age as detected by the comet assay was also reported in other studies [46][47][48][49][50][51]. In contrast, there are studies that showed no effect of age on the level of DNA damage [52][53][54][55][56][57][58]. As the children in our study were in the similar age range spreading over only ten years it was difficult to determine if there is an actual age-difference in DNA damage among them.…”
Section: Discussioncontrasting
confidence: 61%
“…The alkaline Comet assay is a sensitive technique that enables the detection of DNA strand breaks and alkalilabile sites in individual cells [Fairbairn et al, 1995;Holz et al, 1995]. Previous studies carried out using this technique showed that the known NOC carcinogen N-methyl-N-nitro-N-nitrosoguanidine (MNNG) was genotoxic in human colon cells [Pool-Zobel and Leucht, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…He does not present own comet assay results and has not published any, instead he refers to a CV ''in the order of 30 and 40%'' published by Speit et al (2007), obtained by densitometric evaluation of 50 cells per assay. In contrast, published data from others gave an intra-assay variability of 4.1-21.3% (Holz et al 1995), or 0.5-4% (Hughes et al 1997). In addition, the low CV's published by Schwarz et al are not ''in sharp contrast to previously published results''.…”
Section: Areas Of Concernmentioning
confidence: 54%